Net Positive Manifesto: a business case for changing the world - Winston, Andrew (Henry Stewart Talks, 2022)
Corporate social action, Sustainability, ESG, Executive pay gap, Public expectations, Board diversity, Climate change, Business ethics, Social norms, Stakeholder capitalism, Greta Thunberg